Improving The Sustainability of Silage Adoption in Dairy Cattle Farming: Analysis of Determining Factors and Strategies for Increasing Farm Capacity - Reni Suryanti; Maesti Mardiharini; Arif Nindyo Kisworo; Fita Dwi Untari (Jurnal Penyuluhan Pertanian, 2025)
One of the challenges of dairy farming is the availability of feed to meet the needs of livestock. This study aims to 1) identify the potential and problems of utilizing local feed, as well as the potential for implementing silage development; 2) analyze factors that influence the adoption of locally sourced feed innovations; 3) develop strategies for sustainable adoption and increasing the capacity of dairy farmers. This study used a participatory approach involving 47 farmers as a two-year action study (2023–2024). Data collection methods include surveys, in-depth interviews, and focus group discussions (FGDs). Data was analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) to identify factors that influence the adoption of silage innovations. The results of the study showed that the adoption of silage technology was influenced by the characteristics of farmers, the role of extension workers, and the nature of the innovation. Although the potential for local feed is abundant, its utilization is still low due to limited knowledge of farmers and processing infrastructure. The structural model test showed a significant relationship between silage adoption and increased milk productivity (coefficient 0.508; p = 0.008). This study recommends strengthening the institution of livestock farmers through the People's Livestock School (SPR), continuous training, and integration of crop-livestock systems (SITT) to optimize local resources. The proposed design model includes silage-based feed diversification, utilization of agricultural waste, and partnerships with agribusiness actors. This study provides a reference for sustainable agricultural policies and the development of technological innovations that are adaptive to the characteristics of smallholder farmers.